2003
DOI: 10.1094/pdis.2003.87.7.854
|View full text |Cite
|
Sign up to set email alerts
|

Etiology of Phytophthora drechsleri and P. nicotianae (=P. parasitica) Diseases Affecting Floriculture Crops

Abstract: Phytophthora nicotianae and P. drechsleri isolates (n = 413) recovered from eight floricultural hosts at 11 different production sites were described according to compatibility type, resistance to mefenoxam, and amplified fragment length polymorphism (AFLP) profiles. Sample sizes ranged from 2 to 120. In all cases, isolates recovered from a single facility had the same compatibility type and resistance to mefenoxam. AFLP analysis indicated that six clonal lineages of P. nicotianae and two clonal lineages of P.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 19 publications
1
28
0
Order By: Relevance
“…Clonal populations of P. nicotianae were identified as a component of field populations from the same tobacco field in four consecutive years (Sullivan et al 2010) and for isolates from different ornamental plants and production sites (Lamour et al 2003). It was suggested that isolates within the same ornamental nurseries spread by asexually generated propagules, such as hyphal fragments, sporangia, chlamydospores or zoospores (Lamour et al 2003). Furthermore, it was concluded that, at least in citrus orchards in Italy, P. nicotianae reproduced primarily asexually since in the majority of citrus orchards examined only the A1 mating type was found (Cacciola & Magnano di San Lio 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clonal populations of P. nicotianae were identified as a component of field populations from the same tobacco field in four consecutive years (Sullivan et al 2010) and for isolates from different ornamental plants and production sites (Lamour et al 2003). It was suggested that isolates within the same ornamental nurseries spread by asexually generated propagules, such as hyphal fragments, sporangia, chlamydospores or zoospores (Lamour et al 2003). Furthermore, it was concluded that, at least in citrus orchards in Italy, P. nicotianae reproduced primarily asexually since in the majority of citrus orchards examined only the A1 mating type was found (Cacciola & Magnano di San Lio 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The same technique was applied to differentiate isolates causing black shank (Zhang et al 2001) and to identify markers linked to the dominant black shank resistance gene (Johnson et al 2002). Amplified Fragment Length Polymorphism (AFLP), utilized by Lamour et al (2003) to study a population from different floricultural hosts and production sites, enabled the identification of six clonal lineages. Although RAPD-PCR and AFLP have proved valuable within a particular study, results obtained with such fingerprinting tools are not always easily reproducible in different laboratories (Cooke & Lees 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Damping off and blight caused by the Phytophthora species, is one of the most devastating diseases affecting cucurbit and vegetables production in Iran (Etebarian, 2012). Some species such as P. capsici , P. drechsleri and P. melonis can cause strong pathogenicity on pepper, cucurbit, tomato, cantaloupe and ornamental plants that cause damping off disease and rot of crown and root (Lamour et al, 2003; Tabarrae et al, 2011). The genus Phytophthora is a soil borne pathogen and survives in the soils as oospores and mycelia for several years in plant debris (Jee et al, 2001).…”
mentioning
confidence: 99%
“…In Oregon, most of infected trees were within 100 m of trees killed the previous year though occasional long-distance (up to 3 km) dispersal was possible (Rizzo et al 2005). Disease spread between production facilities via movement of plants was also previously reported for P. nicotianae and P. drechsleri (Lamour et al 2003). In the present study, the possible disease spread distance of up to 60 km found among GCN sites is probably specific to commercial trading characteristics during the survey period.…”
Section: Disease Spread Among Gcn Sitesmentioning
confidence: 60%